Upaya Peningkatan Kesehatan Periodontal Siswa SMA Negeri 6 Kabupaten Sinjai Melalui Kegiatan DHE (Dental Health Education) dan SRP (Scaling And Root Planing) - Asdar Gani; Mardiana Adam; Hasanuddin Tahir; Sri Oktawati; Supiaty Supiaty; Arni Irawati Djais; Suryana Mappangara; Fuad Husain Akbar; Adam Malik Hamudeng (Universitas Hasanuddin, 2020)
Periodontal disease is a disease of the teeth and mouth that is commonly found in Indonesian society. Periodontal disease is a common microbial infectious disease in adolescents and adults. This disease is an inflammatory disease originating from bacteria that affects the supporting tissues of the teeth. To overcome periodontal disease, it can be done in at least two ways, namely by carrying out plaque control in the form of proper brushing and periodic tartar cleaning. The objectives of this community service activity are: improving the health of the students 'priodontal network of SMA Negeri 6 Sinjai students, increasing students' understanding of the causes of periodontal disease and how to prevent it, changing the behavior of students and teachers brushing teeth. From the community service activities carried out at SMA Negeri 6 Sinjai, it can be concluded as follows: The prevalence of periodontal disease among students in these schools is still quite high, namely 82.98%. Implementation of oral dental health education (DHE) and scaling care / SRP will improve students' understanding and periodontal health status.